A Short Study on Relationship between ‘ABO’ Blood Groups and Coronavirus Disease 2019 (London Journal of Medical and Health Research, 2024)
A Short study based on 204 patients with RT-PCR and Rapid Antigen Test proven SARS-CoV2 infection occurred in an urban municipality areas of total population more than 2 lakhs from March 2020 to August 2021, finding the relationship of covid -19 positive patients and their blood groups to search the link between susceptibility, severity and mortality with the blood groups. Current clinical observation suggest that gender and age of the patients are important risk factors in the susceptibility of Covid-19 infection. It is evident from the study that among the ABO Blood group system, B positive groups are more affected and AB positive groups are less affected but the severity or complications leading to death is evident among more in Blood Group A Positive and less in O positive cases. Among the negative groups. It has been shown that very less incidence is noted in O negative group. Why the negative groups are least affected, it is not clear to the researchers but it can be studied in details in near future.
Keywords: skin; TDDS; microneedle; microscale fabrication techniques; coating techniques; mechanical properties; therapeutics; COVID-19; coronavirus; ABO Blood Group System; Susceptibility; Severity